Northern Raccoon - William H. Kern (EDIS)
Raccoons are found statewide in Florida in ever-increasing numbers. Urbanization and agriculture often help their population because food becomes more available in these conditions. Therefore, it is not at all uncommon to encounter raccoons near your home or neighborhood. Learn more facts about raccoon biology and how to (legally) solve raccoon problems. This revised 7-page fact sheet was written by William H. Kern Jr. and published by the UF Department of Wildlife Ecology and Conservation, January 2012.